Analisis Metode Clustering Pada Wilayah Berdasarkan Jenis Pencemaran Lingkungan Hidup - Fira Fania; Mustika Azzahra; Agus Perdana Windarto (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
This study uses a grouping model in determining areas based on the type of environmental pollution. This study is a special reference from the government in improving environmental sustainability. The data from this study was taken from the website of the government statistical data provider, BPS (Statistics Indonesia) www.bps.go.id. This research uses the K-Mens method and releases it with RapidMiner software to create 2 clusters, high and low level clusters and see what the contents of the cluster are. From the research results obtained by high cluster centroid data that is ((1527), (810.4), (5865), (6655.3), (323), (315.1)) low cluster namely ((139.25) , (122.5), (508,833), (919,222), (64,417), (94,444)). With this analysis, it is expected to be able to load and information for the government to pay more attention to regions whose income is still below average.